THE POLITICS OF LAW CONCERNING THE TENURE OF VILLAGE HEAD REVIEWED FROM THE CONSTITUALISM PERSPECTIVE - Achmad Hariri (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
The politics of law is an instrument of law-making to achieve legal objectives, and the objectives of the law-making must be in line with the constitutional norms. The constitution is a foundation rule for law-making (the politics of law), and in its development, the modern state constitution must be constitutionalism. Constitutionalism is an idea that the constitution must limit the power to hinder the abuse due to unrestricted power. The politics of constitutional law can be seen in the first amendment, namely, Article 7 of the 1945 Constitution: the tenure of a president is five years and limited to two periods, the 1945 constitution is, therefore, constitutionalism. The power limitation of high state institutions is constitutional, but in Law No. 6 of 2014 concerning Villages, some norms are contrary to the constitution: Article 39 related to the tenure of the village head. The tenure of village head in this article is relatively longer than the executive position in supra-village government, that is six years and can be re-elected for three periods, meaning that the village head can occupy the position for a maximum of 18 years. This tenure is eight years longer than the tenure of the president, governor, regent and mayor, thus, it is likely for the village head to conduct the "abuse of power" and the tenure is against the constitutionalism. Abstrak: Politik hukum merupakan instrumen pembuatan hukum untuk mencapai tujuan hukum, adapun tujuan pembentukan hukum harus sejalan dengan norma Konstitusi. Konstitusi itu merupakan aturan dasar yang menjadi sumber pembentukan hukum (politik Hukum), dalam perkembangannya kemudian konstitusi negara modern itu harus konstitusionalisme, paham konstitusionalisme adalah suatu paham dimana konstitusi harus membatsasi kekuasaan, kekuasaan harus dibatasi untuk menjauhi dari tindakan penyelewengan akibat tidak dibatasinya kekuasaan, dalam politik hukum konstitusi dapat dilihat pada amandemen ke satu yaitu pasal 7 UUD 1945, masa jabatan presiden 5 tahun dan dibatasi dua periode, oleh sebab itu konstitusi UUD 1945 konstitusionalisme. Pembatasan kekuasaan lembaga tinggi negara sudah konstitusional, namun dalam UU No. 6 Tahun 2014 tentang Desa ada norma yang bertentangan dengan konstitusi yaitu pada pasal 39 terkait masa jabatan kepala Desa. Dalam pasal tersebut massa jabatan kepala desa relatif lebih lama dibandingkan dengan jabatan eksekutif di pemerintahan supra desa, yaitu 6 tahun dan dapat dipilih lagi sampai tiga periode, artinya kepala desa dapat menduduki sebagai orang nomor satu di desa sampai dengan delapan belas (18) tahun. Masa jabatan ini relatif lebih lama delapan tahun dibanding jabatan presiden, gubernur, bupati dan wali kota, sehingga kepala desa akan dimungkinkan dapat menyelewengkan kewenangan “abuse of power’ dan masa jabatan tersebut bertentangan dengan konstitusionalisme. Kata Kunci: Politik Hukum, Massa Jabatan Kepala Desa, Konstitusionalisme